Bronchodilator responsiveness using spirometry in healthy and asthmatic preschool children. Issue 2 (3rd January 2013) - Borrego, Luis Miguel; Stocks, Janet; Almeida, Isabel; Stanojevic, Sanja; Antunes, João; Leiria-Pinto, Paula; Rosado-Pinto, José E; Hoo, Ah-Fong
Abstract : Objective: To assess repeatability and reproducibility of spirometry measurements, and bronchodilator responsiveness (BDR), in healthy 3–6-year-old preschool children and those with asthma. Design: Spirometry was performed before and 20 minutes after administering either inhaled placebo (for repeatability) or 400 μg salbutamol (for BDR) on two separate occasions (reproducibility) 3–23 days apart in asthmatic preschoolers and healthy controls. Settings: Lung Function Laboratory, Hospital de Dona Estefania, Lisbon. Participants: Healthy preschool children and those with physician-diagnosed asthma, recruited from local Health Clinics and Outpatient Clinic. Main outcome measures: Paired measurements of forced expired volume in 0.75 s (FEV0.75 ) and forced mid-expiratory flows (FEF25–75 ). Results: Technically successful baseline results were obtained in 86% of children assessed. Paired data were obtained in 43 asthmatic and 22 controls (median (range) age: 5.1 (3.4–6.8) years). Baseline FEV0.75 was significantly lower in asthmatic children (mean (SD): 90 (15)% predicted) than in controls (102 (13) % predicted; p<0.001). Within-occasion coefficient of repeatability following placebo was similar in both groups, being 10.4% in asthma and 13.2% in controls for FEV0.75 . Following bronchodilator, FEV0.75 increased significantly more in asthmatic preschoolers (mean (SD): 15.0 (12) %) than in controls (4.5 (5) %; p<0.001), with no significant difference between groups post-bronchodilator. Between-occasion variability was similar to within-day repeatability in controls, but almost twice as high in asthmatic children. Conclusions: BDR can be assessed reliably using FEV0.75 in wheezy preschoolers, provided within-subject variability and responsiveness in health are taken into consideration.